Board Composition, Corporate Performance, and the Cadbury Committee Recommendation - Dahya, Jay; McConnell, John J. (Journal of Financial and Quantitative Analysis, 2007)
Abstract During the 1990s and beyond, countries around the world witnessed calls and/or mandates for more outside directors on publicly traded companies' boards even though extant studies find no significant correlation between outside directors and corporate performance. We examine the connection between changes in board composition and corporate performance in the U.K. over the interval 1989–1996, a period that surrounds publication of the Cadbury Report, which calls for at least three outside directors for publicly traded corporations. We find that companies that add directors to conform with this standard exhibit a significant improvement in operating performance both in absolute terms and relative to various peer group benchmarks. We also find a statistically significant increase in stock prices around announcements that outside directors were added in conformance with this recommendation. We do not endorse mandated board structures, but the evidence appears to be that such a mandate is associated with an improvement in performance in U.K. companies.